Historia De La Universidad Pública Latinoamericana: Una Visión General - César Ernesto González Coronado; Liliana Ibeth Castañeda Rentería (European Scientific Journal, ESJ, 2018)
This text describes on a synthetic way the history that characterizes the development of public Latin America´s universities. Through an intense literature review three core aspects are identified: enrollment generalization, the growth of private institutions and the politicization within the processes, considered as an essential part of the public universities in the continent. The analysis states that even if they are not negative, these characteristics are by themselves product of a history loaded by the social mobility and by the citizenship formation.